Recent Publications (Quarterly Journal of Economics, 1935)
Recent Publications Get access The Quarterly Journal of Economics, Volume 50, Issue 1, November 1935, Pages 193–198, https://doi.org/10.2307/1882350 Published: 01 November 1935